2006
DOI: 10.1007/s10571-006-9036-x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Postconditionig Initiates Additive Mechanism Necessary for Survival of Selectively Vulnerable Neurons After Transient Ischemia in Rat Brain

Abstract: 1. The aim of this study was to validate the role of postconditioning, used 2 days after lethal ischemia, for protection of selectively vulnerable brain neurons against delayed neuronal death. 2. Eight, 10, or 15 min of transient forebrain ischemia in rat (four-vessel occlusion model) was used as initial lethal ischemia. Fluoro Jade B, the marker of neurodegeneration, and NeuN, a specific neuronal marker were used for visualization of changes 7 or 28 days after ischemia without and with delayed postconditionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
81
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 59 publications
6
81
0
1
Order By: Relevance
“…Earlier, it has been reported that IPoC reduces I/R induced hippocampal damage. 41,42) Further, IPoC also attenuated I/R induced impairment in sensorimotor functions, which may possibly due to its protective effects on cortical neurons and striatum. Earlier, IPoC has been documented to prevent I/R induced damage to cortical neurons and striatum.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Earlier, it has been reported that IPoC reduces I/R induced hippocampal damage. 41,42) Further, IPoC also attenuated I/R induced impairment in sensorimotor functions, which may possibly due to its protective effects on cortical neurons and striatum. Earlier, IPoC has been documented to prevent I/R induced damage to cortical neurons and striatum.…”
Section: Discussionmentioning
confidence: 87%
“…Earlier, IPoC has been documented to prevent I/R induced damage to cortical neurons and striatum. 42) Collectively, these protective effects of IPoC on hippocampus, cortex and striatum were manifested in the form of reduction in cerebral infarct size, measured by both volume and weight methods. Moreover, there was a direct correlation between the degree of infarction and impairment in behavioral functions (memory and sensorimotor), as already reported in earlier papers from our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…1 To date, early brain ischemic postconditioning has been first reported in focal ischemia, [3][4][5] then delayed postconditioning against focal 6 and in global ischemia. 7 We have previously shown that hypoxic preconditioning (8% O 2 , 1 hour) performed 24 hours before focal cerebral ischemia in adult mice protects the brain. 10 Furthermore, we reported in vitro a neuroprotective effect of hypoxic preconditioning (0.1% O 2 , 1 hour) when performed 24 hours before OGD on neurons.…”
Section: Discussionmentioning
confidence: 98%
“…[3][4][5] More delayed ischemic postconditioning, starting 6 hours and 24 hours after focal and global cerebral ischemia, respectively, has been also recently described. 6,7 Whereas the molecular mechanisms of cerebral ischemic preconditioning were addressed in many studies, 1 those of postconditioning after focal ischemia were only suggested in a few studies. The protection has been associated with the activation of the protein kinase Akt.…”
mentioning
confidence: 99%
“…However, the prevention of inhibition of translation does not assure survival of CA1 neurons (Burda et al 2003). But endogenous defense mechanism known as ischemic tolerance inevitably needs recovery of protein synthesis (Burda et al 2005(Burda et al , 2006.…”
Section: Discussionmentioning
confidence: 99%